Meutaloe Wareeh Agricultural Empowerment Model in Organic Rice Farming Groups in North Aceh - Suadi Suadi; Abdullah Akhyar Nasution; Isbahannur Isbahannur (Indonesian Center for Religion and Society Studies (InTReSt), 2025)
This study aims to develop and analyze the effectiveness of the Meutaloe Wareeh agricultural empowerment model in organic rice farmer groups in North Aceh. Meutaloe Wareeh is a local wisdom approach rooted in the values of cooperation and togetherness in Acehnese society, which is applied in sustainable agricultural land management. This model integrates organic farming practices with the principles of active farmer participation, environmentally friendly natural resource management, and capacity building through training and mentoring. The results of the study indicate that the implementation of the Meutaloe Wareeh model significantly increased organic rice productivity and farmer welfare in North Aceh. In addition, this model has succeeded in reducing farmer dependence on chemical agricultural inputs and increasing local food security. Factors such as community commitment, government support, and access to organic markets have also played a role in the success of this model. However, challenges related to technology adaptation and climate change are still major concerns. Overall, the Meutaloe Wareeh model has proven great potential as a holistic and sustainable agricultural empowerment strategy, which can be replicated in other areas with adjustments to the local context.